Chemical and mineralogical characterization of silicon manganese iron slag as railway ballast - Oliveira,Ralph Werner Heringer (2017)
Abstract In nature, metal ores such as iron, lead, aluminum and others are found in an impure state, sometimes oxidized and mixed with silicates of other metals. During casting, when the ore is exposed to high temperatures, these impurities are separated from the molten metal and can be removed. The mass formed by these compounds is slag. Slag is the co-product of the smelting of ore to purify metals. It may be considered a mixture of metal oxides, but may also contain metal sulphites and metal atoms in their elemental form. After it is reprocessed to separate the metals contained, the co-products of this process can be used in cement, rail ballast, road paving and various other purposes. The objective of this research work is the presentation of the chemical and mineralogical characterization tests of the silicon-manganese iron slag with the purpose of reusing the co-product as rail ballast. X-ray diffraction tests, quantitative chemical analyzes, scanning electron microscopy and free lime content were prepared for these characterizations. The results of these tests showed the technical feasibility of using slag as rail ballast.